Understanding Dividend Decisions in ASEAN Healthcare Firms: A Policy-Driven Empirical Perspective - Rani, Jyoti; Mittal, Sangeeta (Organizations and Markets in Emerging Economies, 2026)
ASEAN nations’ healthcare sectors have grown as a result of rising healthcare demand, demographic shifts and increased government participation in health finance. In this context, dividend policy is an important financial choice since it signals stability of a company and success to investors while balancing reinvestment demands in a capital-intensive industry. Looking at the importance of the healthcare sector, the present research empirically examines the dividend policy decisions of publicly listed healthcare firms across ASEAN countries from 2019 to 2023 and sees how firm-specific characteristics and important macroeconomic variables, i.e., government healthcare expenditure, GDP and inflation, affect them. The study uses Pooled OLS on the panel data from selected ASEAN nations, with the random effects model chosen using the Hausman test. The result of overall ASEAN countries exhibits that all firm-specific and macro-economic variables, except inflation, exert a significant impact on the dividend payout ratio. Further, the present study uses the Generalised Method of Moment of the Arellano-Bond to address the issue of endogeneity and support the findings that we draw. Overall, the initial panel regression results are substantially supported by the GMM estimate results. In the context of ASEAN healthcare firms, this study fills the theoretical and contextual gap by examining the combined impact of macroeconomic variables (i.e., government healthcare expenditure, GDP and inflation) and firm-specific variables on dividend payout ratio. From the policy standpoint, the results show that continuous and predictable government healthcare funding might influence corporate payment behavior and minimize uncertainty in financial planning of the healthcare sector.
Keywords: dividend policy; firm-specific; macroeconomic; random-effects model; fixed-effects model; ASEAN nations